Social Skills for Youths with Visual Impairments: A Meta-Analysis. (November 2013) - Botsford, Kathryn D.
Introduction: This meta-analysis reviewed correlational research on youths (ages 13–21) with visual impairments (that is, blindness or low vision) conducted using the National Longitudinal Transition Study-2 (NLTS2). Methods: After a systematic literature review, six studies (four peer-reviewed articles, one dissertation, and one conference presentation) met inclusionary criteria and provided sufficient findings for meta-analysis. Three studies were selected to represent NLTS2 Waves 1, 3, and 4 without violating assumptions of independence. The fixed-effect meta-analysis tested the summary effect of social skills variables. Results: Social skills had a moderate summary effect (r 2 = .373), with high precision for an aggregated sample of 1, 229 youths. The test for heterogeneity (I 2 = 94.25) indicated that social skills explained 6% of the between-study findings. Cumulative analysis suggested a small amount of publication bias. Discussion: Although differences other than social skills accounted for most between-study variances, trends in the research imply relationships between social skills and the Expanded Core Curriculum (ECC). Implications for practitioners: Given the limited time available for specialized instruction, identifying ECC areas with measurable positive impacts empowers teachers to design effective programs. The moderate positive overall effect for social skills variables reported in this study supports the continued emphasis on social competence in the educational programs for youths with visual impairments. Given the challenges with conducting research using small samples in the field of visual impairment, meta-analysis offers opportunities to test the overall effect of interventions by combining the findings of multiple smaller studies. This study demonstrated that meta-analytic research is applicable to the field of visual impairment. Future meta-analytic studies of any ECC variables would benefit from the inclusion of additional sources of quantitative research (that is, intervention studies and different large-scale datasets). New research from a variety of data sources would allow the field to more clearly describe trends and relationships among ECC variables and transition outcomes for this population.